Legacy and emerging organic pollutants in indoor and outdoor environments in Africa: Contamination levels, health risks, and analytical techniques - Godfrey Muhwezi; Christine Kyarimpa; Ivan Gumula; Christine Betty Nagawa; Solomon Omwoma; Henry Matovu; Julius Matsiko; Silver Odongo; Douglas Sifuna; Ivan Špánik; Charles Drago Kato; Patrick Ssebugere (Emerging Contaminants)
The World Health Organisation reported that over 20 % of the global disease burden and deaths are caused by environmental factors such as air and dust pollution. Legacy organic pollutants (LOPs) and emerging organic pollutants (EOPs) are among the biggest contributors to this burden. Herein we reviewed literature published for the period 2000–2023 on selected LOPs and EOPs in indoor dust and outdoor air in Africa to understand the occurrence, associated human health risks and common analytical techniques used to identify and quantify these contaminants. The findings revealed generally lower contamination levels for most pollutants than that in most regions outside Africa except for PCBs in outdoor air and OCPs in indoor settled dust. Apart from a few studies for polychlorinated biphenyls (PCBs), most studies reported hazard index (HI) values less than 1 for outdoor air and indoor dust exposure, which suggested negligible non-carcinogenic risks in children and adults. Gas Chromatography and mass spectrometry were the most frequently used analytical techniques for both air and dust probably due to their sensitivity and selectivity in detecting chemical traces at the pg m−3 and ng g−1 levels. Although the current contamination levels are generally low, their synergistic and cumulative effects may in the long run affect the environment and human health. There is also a paucity of data on most contaminants, especially for PCNs, and PFASs in both outdoor air and dust. Coordinated efforts are needed to limit the trade, importation, and disposal of products containing LOPs and EOPs in Africa.